HIIT vs MICT on Male Reproductive Function in a Diabetic Model: A Review of the Benefit-to-Volume Ratio - Sipahutar, Natasha Novida (Universitas Sam Ratulangi, 2025)
Diabetes mellitus impairs male reproductive function through hyperglycemia-induced oxidative stress, hormonal disruption, and testicular damage. This structured literature review evaluated the effects of high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT) on reproductive outcomes in streptozotocin-induced diabetic rodents. Studies reporting sperm quality, testosterone, oxidative stress markers, and testicular morphology after exercise interventions were synthesized narratively. Across the included studies, HIIT was associated with rapid increases in testosterone and sperm motility, alongside reductions in lipid peroxidation and apoptosis, mainly through acute metabolic stimulation and enhanced Leydig cell responsiveness. In contrast, MICT produced slower but more stable improvements, characterized by better spermatogenesis and sustained enhancement of antioxidant capacity, consistent with exercise-induced hormesis and improved insulin sensitivity. These findings suggest that HIIT and MICT act through distinct yet complementary physiological pathways and can be tailored to therapeutic goals and disease severity. Nevertheless, conclusions should be interpreted cautiously due to heterogeneity in streptozotocin dose, training intensity, and intervention duration.